The Moderating Effect of Authentic Leadership on Social Pressure and Budgetary Slack Relationship: An Experimental Investigation - Fatiha, Aliya Tiara; Rohma, Frida Fanani; Kurniawan, Fitri Ahmad (Journal of Leadership in Organizations, 2025)
Introduction/Main Objectives: This research investigates the moderating effect of authentic leadership on social pressure and budgetary slack. Background Problems: Social pressure is an essential element that influences individual behavior in the organization. The concept of social pressure in the organization emphasizes obedience and peer pressure. However, the stream of research tends to examine obedience and peer pressure separately. Novelty: This research examines the differences between obedience pressure and peer pressure in a testing model by considering the moderating effect of authentic leadership. Research Methods: This study employs an experimental approach with a 2x2 factorial design between subjects involving 100 accounting students. Social pressure was manipulated into two conditions: obedience vs. peer. Authentic leadership is categorized into two categories, namely high vs low. Findings/Results: This research found that the creation of budgetary slack occurs for personal interests and regardless of the level of hierarchy in the work environment. This research found that consistent implementation of authentic leadership can reduce the occurrence of budgetary slack. These findings prove that authentic leadership is able to minimize the adverse consequence of social pressure on budgetary slack. Conclusion: This research shows that management can use authentic leadership as an alternative strategy to encourage a more effective budgeting process.